PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMP ISLAM ASWAJA SYAMSUL FALAH PADA MATA PELAJARAN PPKN - Muh. Tahir; Mohamad Mustari; M. Samsul Hadi; Muh. Zubair (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This reseach aims to apply the Teams Games Tournament (TGT) cooperativelearning model in an effort to increase the learning motivation of eighth gradestudents of Aswaja Syamsul Falah Islamic Middle School in the subject of PPKn.The method used is Classroom Action Research, with data collection techniquesincluding observation, questionnaires, and documentation. The research stagesinclude initial observation, planning, implementation of actions, observation duringthe action, and reflection. The subjects of this study were eighth grade students ofAswaja Syamsul Falah Islamic Middle School. The results of the study in Cycle I,the implementation of the Teams Games Tournament (TGT) cooperative learningmodel reached 48%, while the increase in student learning motivation reached56%. Furthermore, in Cycle II, the implementation of the Teams GamesTournament (TGT) cooperative learning model increased to 76%, and studentlearning motivation reached 76%. Then in Cycle III, the Teams Games Tournament(TGT) cooperative learning model succeeded in reaching 96%, and studentlearning motivation increased to 97%. Thus, it can be concluded that thecooperative learning model of the Teams Games Tournament (TGT) type canincrease the learning motivation of class VIII students of Aswaja Syamsul FalahIslamic Middle School in the PPKn subject.